Unintended Consequences of Screening for Ebola - Faherty, Laura Johnson (Am J Public Health, 2015)
Ebola virus disease (EVD) reached the United States in September 2014, leading the Centers for Disease Control and Prevention to publish screening guidelines to identify patients with high-risk exposures at their first point of contact with the health care system. In West Africa, the burden of EVD is superimposed on the trauma of decades of civil war, violence, and poverty. Therefore, an important consideration in implementing screening procedures in the United States is the potential to unintentionally exacerbate posttraumatic stress disorder, or add additional stress from stigma and discrimination, among the West African diaspora. We recommend rigorous research to develop and implement evidence-based, trauma-informed approaches to screening for communicable diseases during outbreaks, using principles of community-engaged or community-based participatory research.